Research progress on the brewing techniques of new-type rice wine - Jiao, Aiquan; Xu, Xueming; Jin, Zhengyu (Food chemistry, 2017)
•Numerous technology innovations of Chinese rice wine (CRW) have greatly impacted on CRW industry.•Reviews related to the research progress in CRW field are relatively few.•This article summarizes the new brewing technologies for making Chinese rice wine.•Various issues are addressed relating to prospects for the CRW industry. As a traditional alcoholic beverage, Chinese rice wine (CRW) with high nutritional value and unique flavor has been popular in China for thousands of years. Although traditional production methods had been used without change for centuries, numerous technological innovations in the last decades have greatly impacted on the CRW industry. However, reviews related to the technology research progress in this field are relatively few. This article aimed at providing a brief summary of the recent developments in the new brewing technologies for making CRW. Based on the comparison between the conventional methods and the innovative technologies of CRW brewing, three principal aspects were summarized and sorted, including the innovation of raw material pretreatment, the optimization of fermentation and the reform of sterilization technology. Furthermore, by comparing the advantages and disadvantages of these methods, various issues are addressed related to the prospect of the CRW industry.